Land use change alters the radiocarbon age and composition of soil and water-soluble organic matter in the Brazilian Cerrado - James, Jason N.; Gross, Cole D.; Dwivedi, Pranjal; Myers, Tyler; Santos, Fernanda; Bernardi, Rodolpho [UNESP]; Faria, Marianne Fidalgo de [UNESP]; Guerrini, Iraê Amaral [UNESP]; Harrison, Rob; Butman, David (Elsevier, 2019)
The Brazilian Cerrado has undergone extensive land-use change in the past century with large areas converted to agriculture and silviculture. Eucalyptus is the dominant planted tree species in Brazil, but the short rotations (6–7 years) and the associated soil disturbances can reduce soil organic matter (SOM), particularly in subsurface soil over long timeframes. SOM is critical to the continued productivity of forests and may be particularly important in Oxisol soils, which underlie much of Brazil. These soils are low in cation exchange sites and rely upon SOM for nutrient and water retention. However, the mechanisms that drive SOM loss under Eucalyptus remain unclear. This study examines both bulk soil and water-soluble organic matter chemistry deep into the soil profile (1.3 m) in paired Eucalyptus and Cerrado forest stands to identify changes in biodegradability, radiocarbon age, and functional group composition that may explain long-term declines in SOM stocks. We hypothesize that changes in litter quality associated with the conversion of Cerrado forest to Eucalyptus plantations increases the content of aliphatic functional groups in water soluble organic matter (WSOM) more quickly than bulk SOM, which drives subsoil accumulation of aliphatic organic moieties through hydrophobic interactions with soil minerals. By utilizing a suite of spectroscopic techniques ( 1 H nuclear magnetic resonance and Fourier transform infrared spectroscopy) alongside isotopic and incubation techniques, this study found substantial shifts toward aliphatic functional group composition in WSOM in both Eucalyptus stands and deeper soil horizons. The radiocarbon age of WSOM was younger than bulk SOM at every depth but still substantially diverged from modern in B horizons. This observation is consistent with the theory that WSOM is in dynamic equilibrium with mineral adsorbed SOM, and that old organic matter replaced on mineral surfaces by fresh inputs may be leached or further degraded by microbes. Radiocarbon age of bulk SOM was younger under Eucalyptus compared to Cerrado forest and the difference between WSOM and bulk SOM radiocarbon age was much smaller in Eucalyptus soils, which together indicate that microbes may be preferentially consuming older SOM after land-use change. The presence of Cerrado understory in Eucalyptus may be important to maintaining SOM cycling; WSOM biodegradability and microbial biomass was greatly reduced in the Eucalyptus site without any understory. Ecotones with Cerrado understory provide diversity in litter types and rooting strategies, while monoculture Eucalyptus, which is commonly found in stand interiors, may reduce the ability for microbes to maintain active nutrient recycling of organic residues.
Keywords: Cerrado; Eucalyptus; Radiocarbon; Soil carbon; Soil organic matter; Water soluble organic matter